Strategi Segmenting, Targeting dan Positioning Program “Sore Ceria” Pro2 FM LPP Radio Republik Indonesia ( RRI) pada Pendengar Radio Generasi Z - Nur Ismawati, Euis; Dwi Adnjani, Made (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Sore Ceria program is a program broadcasted by PRO2 FM LPP Radio Republik Indonesia (RRI) for Generation Z. In the midst of tight competition among digital media, the “Sore Ceria” program must be able to survive and find new innovations in order to continue to grow and progress. Thus, the right Segmenting, Targeting and Positioning strategies are needed in order to reach the expected target audience and highlight different things (Differentiation) and advantages that are not possessed by other radio programs. This study aims to describe the Segmenting, Targeting and Positioning Strategies carried out by the “Sore Ceria” Program from PRO2 FM LPP Radio Republik Indonesia (RRI) Semarang for Generation Z Radio listeners. Using the Niche Theory or Media Ecology Theory which analogizes that the phenomenon of competition between media industries as an ecological process. This research method uses a descriptive qualitative approach through in-depth interviews with two informants. The implementation of the segmentation strategy for the cheerful afternoon program uses a data-based approach and direct interaction with the audience. Another strategy is to divide segments based on audience interests. In the Targeting strategy, in addition to making Gen Z the main focus, the cheerful afternoon program also opens up space for other audiences such as the young millennial generation to reach a wider audience. By using a multiplatform strategy, the cheerful afternoon program can reach its audience and allow the audience to enjoy a more flexible broadcast program. The cheerful afternoon program is not only present on traditional radio broadcasts but also on on-demand podcasts through the RRI Digital application and Instagram. In the positioning strategy, the afternoon program positions itself as a program that is relevant to the Gen Z lifestyle through a relaxed and interactive delivery style. The cheerful afternoon program utilizes the uniqueness of its approach by utilizing the Music Live Request feature as a differentiation of direct interaction features with the audience. Other uniqueness is also strengthened by collaboration with influencers or inspiring young figures who are close to Gen Z. By combining these various elements, cheerful afternoon has succeeded in positioning itself as a program that is not only competitive but also relevant and sustainable. The study only uses one theory, for further research it is hoped that it can deepen the strategy used using other theories in order to gain a broader understanding.